New Technology: Risks and Gains - Magdalena Klimczuk-Kochańska; Andrzej Klimczuk (The SAGE Encyclopedia of World Poverty, 2015)
New technologies are often radical innovations that change current activities across different areas of social and economic life. At the beginning of the 21st century, some of these technologies are information and communications technology (ICT), nanotechnology, biotechnology, robotics, and artificial intelligence. These innovations stimulate new opportunities for the production, distribution, and consumption of goods and services, and thus can help solve social problems. But they also cause new social risks and inequalities.
Keywords: O30; O33; 330; Economic Growth and Technology; Information and Communication Technology and Poverty; Technology Divide; Technology and Poverty Alleviation